The hidden curriculum of gender in Serbian textbooks - Grozdanovski, Nevena; Bekic, Simona (Norma, 2025)
Many documents in the Republic of Serbia mention gender equality as one of the key concepts and goals of education. However, the literature draws attention to the school as the place of gender inequality reproduction. Textbooks are primary instruments for transmitting both formally prescribed content, as well as implicit messages, including those related to gender. Among other things, various gender stereotypes and inequalities can be reinforced and maintained in this way. The implicit content conveying gender messages is referred to as the hidden curriculum of gender, which, although implicit, can influence students’ behavior and the development of their attitudes toward men and women. The aim of this paper is to provide a systematic review of contemporary research of gender sensitivity in textbooks for primary and secondary schools. To determine the presence of implicit gender messages in Serbian textbooks, a literature analysis of papers written in the period 2006-2025 was conducted. The analysis included six studies about textbooks for primary and secondary schools which focus on the gender dimension, and the data were categorized with regard to the textual or visual representations. The analyzed material reveals a lower representation of women (visually and thematically) in textbooks, a clear stereotyping of the roles of women through the family sphere and men through the professional sphere, as well as a general lack of gender-sensitive language. The authors emphasize the importance of textbooks as soruces of gender (in)equality and provide recommendations for further research.